POTENSI Acacia crassicarpa SEBAGAI BAHAN BAKU PULP KERTAS UNTUK HUTAN TANAMAN INDUSTRI - Sugesty, Susi; Kardiansyah, Teddy; Pratiwi, Wieke (Center for Pulp and Paper, 2015)
Industrial Plantation Forest of Acacia mangium for pulp industry in Indonesia has declined its productivity due to a decrease in the quality of soil on the second cycle and thereafter. Therefore, the alternative raw material for pulp has to be found as a substitute for Acacia mangium. Research on the various ages of Acacia crassicarpa (4; 5 and 6 years old) as the pulp raw material has been done. Pulp was prepared using the kraft process. The optimum cooking condition with target Kappa Number of 15 ± 1 was obtained at 20-22% active alkali, 30% sulfidity, temperature of 165ºC, liquor ratio 1:4 and H factor of 1300. Pulp was then bleached using ECF (Elemental Chlorine Free) process with the sequence of ODEDED and XDEDED. Results showed that pulp yield was high enough and meet the standard requirement according to SNI 6107:2009, Pulp Kraft Putih Kayudaun (LBKP). hollocellulose content of Acacia crassicarpa (79,99-80,87%) and α cellulose content (43,33-48,62%) were higher compared to those of Acacia mangium (<79% and <43%) respectively, while lignin and extractive contents were significantly low. It was found that Acacia crassicarpa of 5 years old resulted in better bleached kraft pulp compared to those of 4 and 6 years old. It is concluded that Acacia crassicarpa has a good prospect to be developed in Industrial Plantation Forest as raw material for pulp. Keywords: Acacia crassicarpa, ages, raw material, ECF, pulp ABSTRAK Hutan Tanaman Industri Acacia mangium untuk industri pulp yang dikembangkan di Indonesia saat ini mengalami penurunan produktivitas akibat penurunan kualitas tempat tumbuh pada daur kedua dan seterusnya. Oleh sebab itu perlu dicari bahan baku alternatif pengganti Acacia mangium. Untuk itu telah dilakukan penelitian terhadap Acacia crassicarpa berbagai umur yaitu 4 ; 5 dan 6 tahun. Pembuatan pulp kertas dilakukan dengan proses kraft. Kondisi pemasakan yang optimal dan memenuhi target bilangan Kappa 15 ± 1, diperoleh pada penggunaan alkali aktif 20-22%, sulfiditas 30%, suhu 165ºC, rasio 1:4 dan faktor H 1300. Pemutihan pulp dilakukan dengan proses ECF (Elemental Chlorine Free) yang dikenal ramah lingkungan dengan tahapan ODEDED dan XDEDED. Hasil pulp kraft putih mempunyai rendemen cukup tinggi dan memenuhi pesyaratan spesifikasi SNI 6107:2009, Pulp Kraft Putih Kayudaun (LBKP) kecuali indeks sobek. Kayu Acacia crassicarpa mempunyai kadar holoselulosa (79,99-80,87%) dan selulosa alfa (43,33-48,62%) yang cukup tinggi bila dibandingkan dengan Acacia mangium (<79% dan <43%), serta kadar lignin dan ekstraktif yang cukup rendah. Kayu Acacia crassicarpa umur 5 tahun menghasilkan pulp kraft putih paling baik dibandingkan umur 4 dan 6 tahun. Dengan demikian, kayu Acacia crassicarpa mempunyai potensi untuk dikembangkan di Hutan Tanaman Industri sebagai bahan baku pulp. Kata kunci: Acacia crassicarpa, umur, bahan baku, ECF, pulp